Achieving Internationally Competitive Rail Freight for Coal - The Hunter Valley Rail Project (The Australasian Institute of Mining and Metallurgy, 1995)
The Hunter Valley Rail Project (HVRP) represents most of the coal producers using the Hunter Valley Rail System in NSW to haul coal to the port of Newcastle. This system carries over 70 per cent of NSW's coal exports, comprising over 30 per cent of total Australian coal exports. Hunter Valley coal is the largest export industry in NSW, and one of its largest export growth opportunities. However, the industry is under intense pressure in international markets from existing and new coal producers and from other energy sources. Whilst potential growth in demand is substantial, particularly for thermal coal in Asia, excess world supply has pushed prices down, and this underlying trend may well continue. The industry has lost international competitiveness and as a result, investment has dropped 44 per cent over the last two years. The industry must be rapidly structured to compete and attract investment on the basis that these pressures will continue. Substantial productivity improvement and cost reductions must be made for the industry to regain competitiveness, otherwise growth will not occur and the industry will decline, with serious implications for the Australian and NSW communities. The introduction of internationally competitive rail freight rates is an urgent and essential part of this process. It is the key objective of the HVRP.